Host CDK-1 and formin mediate microvillar effacement induced by enterohemorrhagic Escherichia coli - Cheng-Rung Huang (Nature Portfolio, 2021)
Enterohemorrhagic Escherichia coli (EHEC) induces formation of attaching and effacing lesions in the intestine. Here, Huang et al. use human intestinal cells and a C. elegans model of infection to show that the process is mediated by a host signaling pathway involving cyclin-dependent kinase CDK1 and formin CYK1.